2021
DOI: 10.3390/agronomy11122461
|View full text |Cite
|
Sign up to set email alerts
|

Computational Interaction Analysis of Sirex noctilio Odorant-Binding Protein (SnocOBP7) Combined with Female Sex Pheromones and Symbiotic Fungal Volatiles

Abstract: Sirex noctilio, a major forestry quarantine pest, has spread rapidly and caused serious harm. However, existing methods still need to be improved because its olfactory interaction mechanisms are poorly understood. In order to study the role of male-specific protein SnocOBP7 in the protein–ligand interactions, we selected it as the object of computational simulation and analysis. By docking it with 11 ligands and evaluating free binding energy decomposition, the three best binding ligands were found to be femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Among the 14 ligands, we identified two sex pheromone molecules, three host plant volatiles, and three symbiotic fungal volatiles with higher binding affinity, with (Z)-7-heptacosene, (Z)-9-nonacosene, and (-)-globulol binding most highly stable. In a molecular docking and molecular dynamics study of SnocOBP7 with 11 odorant molecules, Li et al found that SnocOBP7 bound most stably to (Z)-7-heptacosene, (Z)-7-nonacosene and (-)-globulol [52], which was consistent with our results. In the study of the interaction mechanism of RpadOBP3 from Rhopalosiphum padi with (E)-β-farnesene(EβF), Fan identified three amino acid residues in the hydrophobic structural domain, TRP71, TRP68, and PHE2, bound tightly to EβF [53].…”
Section: Discussionsupporting
confidence: 91%
“…Among the 14 ligands, we identified two sex pheromone molecules, three host plant volatiles, and three symbiotic fungal volatiles with higher binding affinity, with (Z)-7-heptacosene, (Z)-9-nonacosene, and (-)-globulol binding most highly stable. In a molecular docking and molecular dynamics study of SnocOBP7 with 11 odorant molecules, Li et al found that SnocOBP7 bound most stably to (Z)-7-heptacosene, (Z)-7-nonacosene and (-)-globulol [52], which was consistent with our results. In the study of the interaction mechanism of RpadOBP3 from Rhopalosiphum padi with (E)-β-farnesene(EβF), Fan identified three amino acid residues in the hydrophobic structural domain, TRP71, TRP68, and PHE2, bound tightly to EβF [53].…”
Section: Discussionsupporting
confidence: 91%
“…Technological advances have the potential to facilitate the development of management tactics for forest insects, including the Symphyta (Slippers et al, 2020). More Symphyta genomes are available, which facilitates the development of new technology such as reverse chemical ecology (Li et al, 2021) or CRISPR‐Cas9 (Pickett, 2014). Accurate identification of Diprionidae pheromone isomers and an increase in compound purity can increase the number of insects caught in ‘attract and kill’ programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational changes when AgamOBP1 bound both N,N-diethyl-3-toluamide and 6-methyl-5-hepten-2-one were investigated by molecular dynamics [50]. According to the existing research, both SnocOBP12 and SnocOBP7 [23] can bind (−)-globuol well. The interaction between SnocOBPs remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The three best binding ligands were found to be female sex pheromones ((Z)-7-heptacosene and (Z)-7-nonacosene) and symbiotic fungal volatiles ((−)-globulol). Five residues played key roles in the binding of each female sex pheromone to SnocOBP7, whereas two residues play key roles in (−)-globulol binding [23].…”
Section: Introductionmentioning
confidence: 99%